Activity System Model, Perceived Self-Efficacy, and Newcomer Integration Behaviour - Almudever, Brigitte; Croity-Belz, Sandrine; Hajjar, Violette (Relations industrielles / Industrial Relations, 2007)
The research presented here contributes to the current debate on the effects of perceived self-efficacy (PSE). The study, undertaken with 157 schoolteachers who had just started their first teaching position, examined the moderating role of PSE on the effects of mismatches between expectations and actual work conditions on newcomer integration behaviour. Based on the theoretical model of multiple socialization, the results suggest that: 1) the degree of exchanges that subjects establish between different areas of their life influences PSE efficiency; 2) PSE effects can be positive or negative depending on the nature of the disturbances to which PSE is applied.